Integrasi Materi Eksponen pada Surah Al-Ikhlas dalam Pembelajaran Matematika - Surani, Nur Eka; Sholihah, Futuha Rohmatish; Al Hakim, M. faris; Risdiana, Syakirna Shifa; Kholil, Mohammad (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2023)
The monotheism value contained in the surah is in the holy book of the Al-Quran, especially in sura Al-Ikhlas. In surah Al-Ikhlas this can be related to exponential material. The purpose of this research is to find out whether there is a relationship between exponential material and surah Al-Ikhlas. Thus, the integration of mathematics and monotheism can help us to gain a broader and deeper understanding of mathematical concepts. The method used in this study is a literature review. The results of this study are (1) The first verse in surah Al-Ikhlas which contains